Self‐Limiting Growth of Ultrathin GaN/AlN Quantum Wells for Highly Efficient Deep Ultraviolet Emitters. Issue 21 (12th August 2019) - Kobayashi, Hirotsugu; Ichikawa, Shuhei; Funato, Mitsuru; Kawakami, Yoichi
Abstract: GaN/AlN ultrathin quantum wells (QWs) emitting in the deep UV spectral range are fabricated by metalorganic vapor phase epitaxy. The GaN thickness is automatically limited to the monolayer (ML) scale due to the balance between crystallization and evaporation of Ga adatoms. This growth characteristic facilitates the fabrication of highly reproducible GaN ML QWs. The strong quantum confinement within the GaN ML QWs achieves emissions below 250 nm. The photoluminescence intensity at room temperature with respect to that at low temperature, which is closely related to the emission internal quantum efficiency, is drastically improved from 0.1% for a conventional Al0.8 Ga0.2 N/AlN QWs to 5% for a 1 ML GaN/AlN (0001) QW and 50% for a 2 ML GaN/AlN (1 1 ¯ 02) QW under weak excitation conditions. These higher emission efficiencies are attributed to the suppressed nonradiative recombination in the GaN QWs and the enhanced radiative recombination in the (1 1 ¯ 02) QW. Abstract : Ultrathin GaN/AlN quantum wells (QWs) on the monolayer (ML) scale drastically improve the emission internal quantum efficiency in the deep ultraviolet spectral range, compared with conventional Al x Ga1− x N‐based QWs. This achievement is attributed to the suppressed nonradiative recombination due to the point‐defect reduction and enhanced radiative recombination in GaN‐based ML QWs.